Changes in symptoms of anxiety, depression, and PTSD in an RCT-study of dentist-administered treatment of dental anxiety - Mariann Saanum Hauge; Tiril Willumsen; Bent Stora (BMC, 2023)
Abstract Background Educating dentists in treatment methods for dental anxiety would increase the patients' access to treatments that are important to their oral health. However, to avoid adverse effects on comorbid symptoms, involvement by a psychologist has been considered necessary. The objective of the present paper was to evaluate whether a dentist could implement systematized treatments for dental anxiety without an increase in comorbid symptoms of anxiety, depression or PTSD. Methods A two-arm parallel randomised controlled trial was set in a general dental practice. Eighty-two patients with self-reported dental anxiety either completed treatment with dentist-administered cognitive behavioural therapy (D-CBT, n = 36), or received dental treatment while sedated with midazolam combined with the systemized communication technique "The Four Habits Model" (Four Habits/midazolam, n = 41). Dental anxiety and comorbid symptoms were measured pre-treatment (n = 96), post-treatment (n = 77) and one-year after treatment (n = 52). Results An Intention-To-Treat analysis indicated reduced dental anxiety scores by the Modified Dental Anxiety Scale (median MDAS: 5.0 (-1,16)). The median scores on the Hospital Index of Anxiety and Depression (HADS-A/D) and the PTSD checklist for DSM-IV (PCL) were reduced as follows: HADS-A: 1 (-11, 11)/HADS-D: 0 (-7, 10)/PCL: 1 (-17,37). No between-group differences were found. Conclusions The study findings support that a general dental practitioner may treat dental anxiety with Four Habits/Midazolam or D-CBT without causing adverse effects on symptoms of anxiety, depression or PTSD. Establishing a best practice for treatment of patients with dental anxiety in general dental practice should be a shared ambition for clinicians, researchers, and educators. Trial registration The trial was approved by REC (Norwegian regional committee for medical and health research ethics) with ID number 2017/97 in March 2017, and it is registered in clinicaltrials.gov 26/09/2017 with identifier: NCT03293342.